The involvement of aquaporin 5 in the inflammatory response of primary Sjogren’s syndrome dry eye: potential therapeutic targets exploration - Fu, Lijuan; Zhao, Zihang; Zhao, Shuang; Zhang, Meiying; Teng, Xiaoming; Wang, Liyuan; Yang, Tiansong (Frontiers in Medicine, 2024)
Sjogren’s syndrome (SS) is a chronic autoimmune disease. Mainly due to the infiltration of lymphoplasmic cells into the exocrine glands, especially the salivary glands and lacrimal glands, resulting in reduced tear and saliva secretion. Reduced tear flow can trigger Sjogren’s syndrome dry eye (SSDE). Although the pathophysiology of SSDE xerosis remains incompletely understood, recent advances have identified aquaporin-5 (AQP5) as a critical factor in dysregulation of the exocrine gland and epithelium, influencing the clinical presentation of SSDE through modulation of inflammatory microenvironment and tear secretion processes. This review aims to explore AQP5 regulatory mechanisms in SSDE and analyze its potential as a therapeutic target, providing new directions for SSDE treatment.